Occurrence of mammalian group A rotavirus in swine population of central India - KUSUMAKAR, A L; ., SAVITA; MALIK, Y P S; ., MINAKSHI; PRASAD, G (The Indian Journal of Animal Sciences, 2011)
This study reports distribution of porcine rotavirus and e~istence of genomic diversity among isolates of porcine rotavirus in central region of India. RNA electrophoresis (RNA-PAGE) results revealed presence of porcine rotavirus with a typical migration pattern of 4: 2: 3: 2, indicative of group Arotavirus. All the porcine rotavirus isolates obtained during the study from different areas showed the saIne type of long electropherotypic migration pattern based on the relative migration of 10th and 11th genome segments. Incidence of PRY in swine population was 25.71% (9/35). The results of age-wise incidence showed that piglets were more commonly infected during early period of life with the highest incidence between 4 and 8 weeks of age (50%), whereas it reduced with age, as piglets above 3 months of age showed incidence of only 7.69%. The results of present study clearly indicate circulation of single strain of porcine rotavirus in this region of the country which can be targeted to make a suitable vaccine. However more data with detailed studies are required on this infection in pigs from central India as well as other parts of the country.Â